Chemometrics methods to determine palm oils iodine value (IV) using FT-NIR and FTIR spectra / Nor Fazila Rasaruddin - Rasaruddin, Nor Fazila (2018)
The authentication of the palm oils quality is indirectly crucial to consumer health. There are issues in palm oils quality within consumer macrocosm such as recycled and adulteration of cooking oils. Recently in Malaysia, there are claims of used cooking oils reprocessed and sold as new with lower price to consumers. This creates a threat to consumer health because they might use the reprocessed cooking oils unknowingly. In this study, the palm oils quality was determined through the iodine value (IV) which measured the total unsaturation of the oils. The characteristic of double bond in the oils was examined before and after oxidation process through the combination of spectroscopic method of Fourier Transform Near Infrared (FT-NIR) and Fourier Transform Infrared (FTIR) analysis and chemometrics methods.